Pendidikan Rumah Tangga Perspektif Hadis - ., Karimah; Jayyidah, Hafizhotul; Lica, Arda Mei (CV. ITTC INDONESIA, 2025)
Household education is a fundamental foundation for shaping creed, character, and the overall quality of family life. This article examines the concept of family education from the perspective of prophetic traditions through a literature-based study of tarbawi-oriented hadiths addressing marital relations, worship habituation, daily manners, and the development of moral culture within the home. The findings indicate that the hadiths emphasize the roles of exemplary conduct, balanced communication, cooperation, and the consistent practice of Islamic values as the main pillars of family education. The hadiths also highlight the moral responsibility of each family member in maintaining a home environment conducive to spiritual and ethical development. These findings affirm that implementing tarbawi principles is essential for building a harmonious and morally grounded Muslim family.